Values Conflict in Virtual Space "A Systematic Approach to the Study of Social Informatics" - Alsawalqa, Rula (Jordan Journal of Social Sciences, 2021)
In light of increasing new media applications, number of users, diversity of quality, age, class and ethnicity, the cyber culture has been formed and new value concepts have contributed to the formation and reshaping social and political awareness of individuals, especially young people in shaping the vision of its users, it also controlled attitudes, patterns of consumption, creativity, expressions and cultural diversity, influenced the processes of self-identification at individual and collective levels. This study clarifies the concept of values conflict and identifies the most prominent topics in the virtual space by guiding the issues of interactive symbolic theory to find out its causes and understand its dimensions. The results found, most prominent topics that raised values conflict of individuals in the economic field is gain and consumption and in the social field, emerged the issue of generational conflict, electronic violence, deepening the lack of social belonging, spread and promote deviant behavior and abnormal sexual orientation. In the political field, reshaping political awareness emerged through the ability promoting new ideologies and political trends in the interest of individuals, their homelands in a way provoking conflict, reviving religious factors returning it to the public field, promote values of loyalty, belonging, emergence of digital citizenship, contributing promotion of principles of democracy and liberation. Regarding the cultural field, phenomenon of alienation, everything related to the identity, cultural specificity of members of society emerged, which was targeted by intellectual cultural invasion, leading to subordination, self-reliance, surrender, and denial of nationalism, national and personal identity.